Bitcoin, Gold, And S&P 500: Strategic Comparison For Future Investments In The Digital Era: English - Arga Abdi Rafiud Darajat Lubis (Argael Publisher, an imprint of CV. ARGA FARMA, 2024)
This study examines the comparative performance of three major asset classes—Bitcoin, gold, and the S&P 500—in addressing inflation and global economic dynamics from 2013 to 2024. Using historical data, the research analyzes price changes, trading volume, and value growth for each asset. Bitcoin recorded extraordinary growth of 8,518.54%, reflecting its widespread global adoption as an innovative digital asset. The S&P 500, a benchmark for stock market stability, achieved cumulative growth of 224.68%, while gold, a traditional safe-haven asset, saw moderate growth of 42.85%. To assess Bitcoin’s future potential, price projections were conducted using the Location Quotient (LQ) method with a Compound Annual Growth Rate (CAGR) of 51.81%. These projections estimate that Bitcoin's price could reach 755,417.95 by 2029, making it a highly promising long-term investment. However, Bitcoin's high volatility remains a key challenge for investors. This study also links asset performance to inflation rates in Indonesia, as reflected in the 58.82% increase in rice prices over the same period. Findings indicate that Bitcoin not only preserves wealth against inflation but also offers significantly higher profit potential compared to traditional assets. This article aims to provide insights for investors in formulating optimal portfolio diversification strategies by weighing the strengths and risks of each asset in the context of the digital age and evolving global economy.